When the East Meets the West: Analysing Rached Ghannouci’s Synthesis of Democracy in Islam - Zulkarnain, Fisher; Muhammad, Aminu Yahaya; Sule, Babayo; Abdul Sahid, Asep (Journal of Al-Tamaddun, 2022)
Democracy is being pushed aggressively on a global scale as the best and final form of government without even an alternative offered to the opposing views by the champions of the system in the 21st century. The main arguments presented by the apologies of democracy is its feasibility of providing and guaranteeing freedom of speech, liberty of choosing a leadership, accountability and transparency. However, this view is being perceived with cynicism in other parts of the world particularly the Islamic world where the absolute sovereignty and laws are referred to from a divine source. Most of the contemporary Islamic scholars are not against democracy except where its principles such as man-made laws are regarded as supreme over the Shari’ah law. But, Rached Ghannouchi, a Tunisian activist and a political leader believed that there is a perfect way to synthesise between the Western liberal democracy and Islamic governance through the side line of political Islam and the full Islamisation of democracy in practice. Ghannouchi’s combination of ideology, philosophy and activism earned him a status of an Islamic democratic philosopher in the 21st century. This study critically examined the efforts made by Ghannouchi in Islamizing democracy using a rhetorical analytical approach of linking and comparing the early Islamic philosophy on democracy and Ghannouchi’s ideas to arrive at a position of policy implication for democratic governance in the Muslim world.